2017
DOI: 10.1080/13596748.2017.1314680
|View full text |Cite
|
Sign up to set email alerts
|

From teacher to manager: expectations and challenge in the further education sector. a relationship model

Abstract: In a turbulent working environment with varying expectations and challenges is it fair to expect further education teachers and managers to maintain and improve standards? This article highlights that with the incorporation of colleges began a series of initiatives to professionalise the FE sector. This coupled with pressures for those who work within it to meet KPIs in a climate of financial constraint and inconsistency of policy decisions led to a culmination of challenges. By reviewing current literature th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Despite this wish to be more involved with learners, the maximum number of hours taught by interviewees was 8 hours per week, with half teaching only when covering for absent colleagues. This result seemed to agree with Corbett’s (2017) assertion of a shift away from an education focus to one that involves far less contact with learners. However, they were still focused on ensuring their departments provided interesting and relevant education and training programmes to attract learners and give them the knowledge and skills they needed to progress.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Despite this wish to be more involved with learners, the maximum number of hours taught by interviewees was 8 hours per week, with half teaching only when covering for absent colleagues. This result seemed to agree with Corbett’s (2017) assertion of a shift away from an education focus to one that involves far less contact with learners. However, they were still focused on ensuring their departments provided interesting and relevant education and training programmes to attract learners and give them the knowledge and skills they needed to progress.…”
Section: Resultssupporting
confidence: 86%
“…It emphasizes the human side of the job, although it also stresses that the end goal is to implement something that has been decided at a senior level. This is supported by both Briggs (2005) and Corbett (2017), who described how academic middle managers are responsible for translating policy into practice. It is clear from the literature (Earley, 1998; Glover et al, 1998) that many interpret their role as one of implementing strategy rather than creating it.…”
Section: The Role Of the Middle Managermentioning
confidence: 92%
See 1 more Smart Citation
“…The impact of corporatisation has had an equally significant influence on management and leadership, in particular the ways in which these roles are enacted. The differences between the two roles has been subject to much debate (Corbett 2017;Northouse 2017;Bolman and Deal 1997) and it is not the intention of this paper to examine, in depth, the various arguments other than to note Courtney's (2015) view that within a neo-liberalist approach, leaders are assumed to be "corporate actors" (2015, 214) who are expected to fulfil a role for the organisation rather than pursue goals driven by values and philosophy. This has clear links with the established corporate model in education where 'managers' are expected to ensure that stakeholders are kept happy (Smith 2007) and given the culture of the sector, this suggests that 'manager' would be an accurate way of describing participants in this research.…”
Section: Literaturementioning
confidence: 99%
“…Beresford and Michels (2014) and Briggs (2005a) discuss the challenge of managers having to ensure that the quality of provision (de facto teaching and learning) is to the highest standard, against a backdrop of ensuring that all other aspects of an FE institutions business are also attended to. This can be very challenging, especially for new managers who are transitioning from teacher to manager (Corbett, 2017; Page, 2013). Yet despite these competing priorities, this paper has found that HR managers agree that quality of provision is a key priority for someone to be an effective FE middle manager.…”
Section: The Four Pillars Of Professional Expectationsmentioning
confidence: 99%